Pengaruh Pengalaman Layanan Dan Strategi Penetapan Harga Pada Kepuasan Pelanggan Nike Store Senayan City Mall - Latifah; Cornelia Dumarya Manik (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this study is to determine the effect of service experience and pricing strategy on customer satisfaction at Nike Store Senayan City Mall, both partially and simultaneously. The method used is quantitative. The sampling technique uses the Slovin formula, and the sample in this study consists of 91 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this study are that service experience has a significant effect on customer satisfaction Y = - 0.625 + 0.993X1, the correlation coefficient value is 0.701, which means that the two variables have a strong relationship. The value of determination or contribution of influence is 0.830 or 83%. The calculated t-value is greater than the table t-value (20.820 > 1.987). Pricing strategy significantly affects customer satisfaction: Y = 5.852 + 0.868X2, with a correlation coefficient of 0.728, meaning that the two variables have a strong relationship. The coefficient of determination or contribution is 0.843, or 84.3%. The t-value is greater than the t-table value (21.850 > 1.987). Service experience and pricing strategy simultaneously have a significant effect on customer satisfaction Y = -1.176 + 0.527X1 + 0.494X2. The correlation coefficient value or the degree of relationship between the independent variable and the dependent variable was obtained at 0.959, meaning that there is a very strong relationship. The coefficient of determination or simultaneous contribution value is 92%, while the remaining 8% is influenced by other factors. The calculated F value is greater than the F table value (506.236 > 3.10). Thus, there is a significant simultaneous influence of service experience and pricing strategy on customer satisfaction.